LIFESTYLE CHANGE AS A TREATMENT FOR TYPE 2 DIABETES: : AN INTEGRATIVE REVIEW - Campos Lopes, Juliana (2021)
INTRODUCTION Lifestyle Medicine (LM) studies the illness process related to lifestyle habits and fosters interventions aiming to prevent and treat chronic diseases such as type 2 diabetes (T2D), which is a metabolic dysfunction closely related to individual lifestyle habits. OBJECTIVE to search the literature for references on lifestyle as a therapeutic approach in patients with Type 2 Diabetes Mellitus. METHODOLOGY this is an integrative review of the scientific literature with a qualitative approach, carried out in July 2021, with a search for articles between 2015-2021 in the various databases. RESULTS AND DISCUSSION 13 articles were included in this review and they showed the relevance of lifestyle change for DM2 prevention and remission. In this sense, weight loss must be prioritized and the treatment covers dietary pattern changes, physical activity, stress control, mental health, and health education promoting self-care for DM2 patients. FINAL CONSIDERATIONS after considering and understanding the advantages of the LM approach in the treatment of DM2, this topic should be increasingly discussed, thus creating new perspectives regarding the health care and quality of life of patients.